Alcohol attributable burden of incidence of cancer in eight European countries based on results from prospective cohort study. (7th April 2011) - Schütze, Madlen; Boeing, Heiner; Pischon, Tobias; Rehm, Jürgen; Kehoe, Tara; Gmel, Gerrit; Olsen, Anja; Tjønneland, Anne M; Dahm, Christina C; Overvad, Kim; Clavel-Chapelon, Françoise; Boutron-Ruault, Marie-Christine; et al.
Abstract : Objective To compute the burden of cancer attributable to current and former alcohol consumption in eight European countries based on direct relative risk estimates from a cohort study. Design Combination of prospective cohort study with representative population based data on alcohol exposure. Setting Eight countries (France, Italy, Spain, United Kingdom, the Netherlands, Greece, Germany, Denmark) participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Participants 109 118 men and 254 870 women, mainly aged 37-70. Main outcome measures Hazard rate ratios expressing the relative risk of cancer incidence for former and current alcohol consumption among EPIC participants. Hazard rate ratios combined with representative information on alcohol consumption to calculate alcohol attributable fractions of causally related cancers by country and sex. Partial alcohol attributable fractions for consumption higher than the recommended upper limit (two drinks a day for men with about 24 g alcohol, one for women with about 12 g alcohol) and the estimated total annual number of cases of alcohol attributable cancer. Results If we assume causality, among men and women, 10% (95% confidence interval 7 to 13%) and 3% (1 to 5%) of the incidence of total cancer was attributable to former and current alcohol consumption in the selected European countries. For selected cancers the figures were 44% (31 to 56%) and 25% (5 to 46%) for upper aerodigestive tract, 33% (11 to 54%) and 18% (−3 to 38%) for liver, 17% (10 to 25%) and 4% (−1 to 10%) for colorectal cancer for men and women, respectively, and 5.0% (2 to 8%) for female breast cancer. A substantial part of the alcohol attributable fraction in 2008 was associated with alcohol consumption higher than the recommended upper limit: 33 037 of 178 578 alcohol related cancer cases in men and 17 470 of 397 043 alcohol related cases in women. Conclusions In western Europe, an important proportion of cases of cancer can be attributable to alcohol consumption, especially consumption higher than the recommended upper limits. These data support current political efforts to reduce or to abstain from alcohol consumption to reduce the incidence of cancer.